Ultrastructural studies of mycobacterial phages isolated from the material of sarcoid patients - Mohelská, H; Wisingerová, E (Journal of hygiene, epidemiology, microbiology, and immunology, 1977)
Mycophages DNAIII, Legendre and Clark, isolated from sarcoid material by Mankiewicz, belongs with respect to their ultrastructural morphology, to the systematic group B according to Bradley or to group IV according to Tikhonenko. These phages contain 2-DNA, their head is a regular icosahedron, the tail consisting of a helix of protein subunits is attached to the head by a narrowed segment and is fixed in it by means of a disc-like structure. It is terminated by a ball-shoped or conical end structure. By their dimensions, these phages belong to the smallest ones in this systematic group. In comparison with other mycobacterial phages, the studied phages exhibit very low mechanical resistance. This characteristic is most pronounced in phage DNAIII. This group of mycophages is also very sensitive lipid solvents and increased temeprature. This phenomenon is also most pronounced in phage DNAIII. The explanation of these findings will be the subject of our further study.
Keywords: Blood; Sputum; sputum; Humans; Mycobacteriophages; Sarcoidosis; sarkoidóza; mykobakteriofágy; lidé; krev